Pelayanan Wire Crane Terhadap Pencapaian Port Time KM. Logistik Nusantara 4 di PT. Pelayaran Nasional Indonesia (PT Pelni) di Jakarta - Cari Arianto; Agung Kwartama (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Ships with efficient port time reflect success in various aspects such as port operations, including time management, coordination between related parties, readiness of facilities and equipment, and workforce reliability. These efficiencies not only benefit port operators and shipping companies, but also contribute to smooth logistics supply chains, lower costs and increase economic competitiveness. Researchers determine 2 (two) types of data, namely secondary data and primary data, which will be processed through interviews and literature. By knowing each of the port time components above, we can understand the key to increasing operational efficiency, reducing costs, and ensuring smooth port and ship operations. Process optimization at each stage of port time implemented can help ports and shipping companies achieve competitive advantage and increase customer satisfaction Keywords: , , ,